Effectiveness of Strategies for Nutritional Therapy for Patients with Type 2 Diabetes and/or Hypertension in Primary Care: A Systematic Review and Meta-Analysis - Galendi, Julia Simões Corrêa [UNESP]; Leite, Renata Giacomini Occhiuto Ferreira [UNESP]; Banzato, Luísa Rocco [UNESP]; Nunes-Nogueira, Vania Dos Santos [UNESP] (MDPI, 2022)
A central aspect to the management of type 2 Diabetes Mellitus (T2DM) and hypertension is promoting a healthy lifestyle, and nutritional therapy (NT) can support patients achieving glycemic control and blood pressure targets. This systematic review aimed to evaluate the effectiveness of NT in the management of patients with T2DM and/or hypertension in primary care. Primary outcomes were HbA1c, systolic blood pressure (SBP) and diastolic blood pressure (DBP). Thirty-nine studies were included, thirty on T2DM and nine on hypertension. With a moderate quality of evidence, educational/counseling programs and food replacement programs in primary care likely reduce HbA1c on patients with T2DM (mean difference (MD): −0.37, 95% CI: −0.57 to −0.17, 7437 patients, 27 studies; MD: −0.54, 95% CI: −0.75 to −0.32, 440 patients, 2 studies, respectively). Mediterranean diet for T2DM was accessed by one study, and no difference between the groups was found. Educational and counseling programs likely reduce DBP in patients with hypertension (MD: −1.79, 95% CI: −3.46, −0.12, 2840 patients, 9 studies, moderate quality of the evidence), but the effect in SBP was unclear due to risk of bias and imprecision. Nutritional therapy strategies (i.e., educational/counseling programs and food replacement programs) in primary care improved HbA1c in patients with T2DM and DBP in individuals with hypertension.
Keywords: chronic disease; health services research; hypertensions; nutrition therapy; primary care; type 2 diabetes mellitus